Analysis of angular momentum in hurdling by world and japanese elite sprint hurdlers - Shibayama, K.; Fujii, N.; Shimizu, Y.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The purpose of this study was to investigate the characteristics of the angular momentum of the limbs during the airborne phase of sprint hurdling. Twenty-nine male hurdlers participated in this study. Their hurdling motions at the seventh hurdle were videotaped using two high-speed cameras. During the first half of the airborne phase, the faster hurdlers required a large angular momentum of the lead leg, which they compensated for by a large counter direction of angular momentum in the trail leg. During the second half of the airborne phase, faster hurdlers swung the lead leg for a shorter duration by adjusting the head and trunk. However, if hurdlers overemphasise the downward motion of the lead leg, this can result in excessive backward and left leaning of the trunk upon landing.